Criminogenic and Desistance-Promoting Processes Behind Bars and Postrelease Supervision: New Evidence From Federal Offenders. (March 2020) - DeLisi, Matt; Drury, Alan; Elbert, Michael
Institutional misconduct has criminogenic implications, whereas visitation, work, and educational involvement have desistance implications, but there is considerable heterogeneity in the inmate population and in the effects of institutional experiences and various programming on their immediate and postrelease behavior. Using a near population of offenders on federal supervised release, the current study examined the effects of criminogenic (e.g., misconduct) and desistance-promoting (e.g., work, education, and visitation) factors occurring within prison along with the effects of importation factors (e.g., arrest onset, federal criminal history rank, and demographics) in relation to functioning/compliance on supervised release. Institutional misconduct and specifically drug/alcohol misconduct reduced postrelease functioning/compliance, while the effects for visitation were limited. Prison work and educational experiences had no effect on supervised release outcomes. The most consistent predictor of supervision failure was age of arrest onset and to a lesser extent federal criminal history rank that is supportive of importation and life-course perspectives.